2015
DOI: 10.1016/j.compscitech.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of nano-particle additives in Kevlar® 29 impact resistant composites

Abstract: openAccessArticle: Falsecover date: 2015-09-08pii: S0266-3538(15)00194-3Harvest Date: 2016-01-06 13:07:53issueName:Page Range: 41-41href scidir: http://www.sciencedirect.com/science/article/pii/S0266353815001943pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…2 Furthermore, to avoid failures in the composite during a ballistic event, it is necessary that the high impact energy applied to it is absorbed within a short time frame. 10 For instance, some studies analyzed ballistic impact in thermoset polymer composites, 7,11-13 e.g. Omidvar et al 7 prepared epoxy/calcium carbonate/Kevlar (29/49 and 129) composites with epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, to avoid failures in the composite during a ballistic event, it is necessary that the high impact energy applied to it is absorbed within a short time frame. 10 For instance, some studies analyzed ballistic impact in thermoset polymer composites, 7,11-13 e.g. Omidvar et al 7 prepared epoxy/calcium carbonate/Kevlar (29/49 and 129) composites with epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…Albert et.al. reported a 7.3–8% increase in impact resistance of MWCNT‐enriched epoxy/Kevlar laminate as compared to neat epoxy/Kevlar laminate . Laurenzi et al reported that the addition of functionalized MWCNT at 0.5 wt% in epoxy Kevlar‐29 laminates increases absorption energy by up to 56% as compared to neat epoxy Kevlar laminates .…”
Section: Introductionmentioning
confidence: 99%
“…Manero II et al studied the effects of nanofiller additives when used in Kevlar 29 by creating composites by impregnating Kevlar 29 with dispersions of nanoparticle additives and milled carbon fiber in a thermoset resin system that was an unmodified liquid epoxy resin based on Bisphenol‐A. The nanoparticle additives used were CNTs and a 33% concentrate core shell rubber (CSR) toughening agent.…”
Section: Armormentioning
confidence: 99%
“…Lastly, while the previous sections discussing composite materials and their interfaces have largely focused wearable devices for civilian, controlled environments, there is a significant body of work focusing on improving composite material interfaces for national defense. These largely center on armor materials, and more specifically direct their efforts toward improving the synthetic fiber Kevlar . The most important factors when monitoring the performance of Kevlar include ballistic resistance, stab resistance, and other forms of energy absorption and dissipation.…”
Section: Introductionmentioning
confidence: 99%